2015
DOI: 10.1371/journal.pone.0134918
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Antiretroviral Adherence and Virological Outcomes in People Living with HIV in the Highlands of Papua New Guinea

Abstract: Adherence to antiretroviral therapy (ART) is paramount for virological suppression and positive treatment outcomes. ART has been rapidly scaled up in Papua New Guinea (PNG) in recent years, however clinical monitoring of HIV+ individuals on ART is limited. A cross-sectional study was conducted at two major sexual health clinics in high HIV prevalence provinces in the Highlands Region of PNG to assess ART adherence, factors affecting adherence and the relationship between ART adherence and virological outcomes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
25
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 29 publications
7
25
2
1
Order By: Relevance
“…The higher viral load suppression among men was also observed in a multi-center cohort study in Canada that found the male sex as one of the predictors of the likelihood of viral load suppression [29]. The failure of viral load suppression in 8/98 (8%) was comparable to the cross-sectional study from Papua New Guinea by Gare et al where evidence of virological failure was shown in 12/95 (12%) of their patients [30].…”
supporting
confidence: 68%
“…The higher viral load suppression among men was also observed in a multi-center cohort study in Canada that found the male sex as one of the predictors of the likelihood of viral load suppression [29]. The failure of viral load suppression in 8/98 (8%) was comparable to the cross-sectional study from Papua New Guinea by Gare et al where evidence of virological failure was shown in 12/95 (12%) of their patients [30].…”
supporting
confidence: 68%
“…The majority of studies (18) were from low-income and middle-income countries. [20][21][22]24,25,[27][28][29][30][33][34][35][40][41][42][43][44]46 Studies provided data for 72,119 participants, sample sizes ranged from 76 to 3700 adults, with 31,011 men and 40,669 women included (1 study did not disaggregate data by sex). 46 Median baseline CD4 count ranged from 104 to 486 cells per microliter and was FIGURE 2.…”
Section: Resultsmentioning
confidence: 99%
“…In this sense, the dialogue with the health professionals is fundamental to the understanding of the treatment system to all doubts of patients be resolved [21]. Moreover, HAART patients need to be encouraged to understand the mechanisms of the disease so that they can adapt to necessary changes in regular and continuous use of therapy and be aware of the requirements that make the complex treatment [22].…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged duration of the system also interfere negatively in membership in view of the changes resulting from prolonged use of therapy. Study found that some changes caused by the use of prolonged treatment, such as anemia, renal complications, metabolic and lipodystrophy were factors related to the abandonment of treatment and consequent lack of membership [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation